Hiss me deadly - James, Miranda (Cat in the stacks mystery, 2024)
"Charlie and Diesel must catch a killer before he strikes another deadly note in this latest installment of the New York Times bestselling Cat in the Stacks Mysteries. Charlie Harris remembers Wilfred "Wil" Threadgill as one of the outsiders during high school in Athena. Although Wil was a couple of years ahead of him and his friend Melba Gilley, Melba had a big crush on Wil, who dropped out after his junior year. An aspiring musician, Wil hit the road for California and never looked back. Wil eventually became a star, fronting a band and writing award-winning songs. Coming back to Athena to work for two weeks with students in the college music department, Wil is now the big man on campus. Not everyone is happy to have him back, however. His entourage have been the target of several acts of petty harassment. At first they are easy for Wil to shrug off, but the incidents escalate and become more troubling. When one of the band members is killed, Charlie worries that Melba, now deeply involved with the man at the center of the attacks, could be in deadly danger. It is up to Charlie and Diesel to find out who hates Wil Threadgill enough to silence his song . . . forever!"--